Residual phosphate fertilization and Azospirillum brasilense in the common bean in succession to maize intercropped with Marandu grass (Revista Ciência Agronômica, 2017)
One of the alternatives for achieving sustainable agriculture and a reduction in production costs, especially withphosphate fertilisers, is to inoculate seeds with bacteria of the genus Azospirillum. The aim of this study therefore, was to evaluateresidual phosphate fertilisation and Azospirillum brasilense, together with the contribution of straw from maize intercroppedwith Marandu grass, on leaf nutritional content, yield components and winter bean yield. The experiment was carried out on theTeaching and Research Farm, of the School of Engineering at UNESP, located in Selvíria in the State of Mato Grosso do Sul, in atypic clayey dystrophic Red Latosol. The experimental design was of randomised blocks with four replications in a 5 x 2 factorialscheme. The treatments consisted of beans sown on straw from maize intercropped with Marandu grass on areas that had receivedfive levels of P2O5in the form of MAP, applied during an initial cultivation of black oats (0, 30, 60, 120 and 240 kg ha-1), both withand without inoculation of the oat and maize which preceded the beans with Azospirillum brasilense. Leaf nutrient content, leafchlorophyll index (ICF), yield components and bean productivity were all evaluated. Inoculation with Azospirillum brasilense ofthe black oat and maize seeds improved the nutritional status of the plants, but had a negative effect on grain yield. Fertilisation ofthe oat crop with phosphorus had a positive residual effect on the beans, with increases in yield components and grain yield.